1991
DOI: 10.1182/blood.v77.1.84.bloodjournal77184
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cell-surface antigen associated with activated T lymphoblasts and activated platelets

Abstract: We have identified and biochemically characterized an antigen, 8A3, which is expressed on activated T lymphoblasts and activated platelets. Monoclonal antibodies to 8A3 were raised against the primitive lymphoid/myeloid cell line KG1a and additionally bound to the erythroleukemia-derived cell line HEL, whilst exhibiting little or no reactivity with a panel of other hematopoietic cell lines. The 8A3 antigen was expressed on poorly differentiated T-cell leukemias and on phytohemagglutinin-activated T-cells maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
69
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 25 publications
3
69
1
Order By: Relevance
“…These contradictory results are either explained by the use of different CD109 mAbs or by differences in platelet preparation and buffers used. The mAbs 1B3 and 8A3 do not react with resting platelets but, in both cases, platelets were obtained by gel filtration in the presence of inhibitors of activation such as prostaglandin I 2 and acetylsalicylic acid (Sutherland et al, 1991;Bordin et al, 1997). Previous studies with mAb D2 showed binding to platelets obtained from standard platelet concentrates (Haregewoin et al, 1994), and this is confirmed in the current study.…”
Section: Discussionsupporting
confidence: 85%
“…These contradictory results are either explained by the use of different CD109 mAbs or by differences in platelet preparation and buffers used. The mAbs 1B3 and 8A3 do not react with resting platelets but, in both cases, platelets were obtained by gel filtration in the presence of inhibitors of activation such as prostaglandin I 2 and acetylsalicylic acid (Sutherland et al, 1991;Bordin et al, 1997). Previous studies with mAb D2 showed binding to platelets obtained from standard platelet concentrates (Haregewoin et al, 1994), and this is confirmed in the current study.…”
Section: Discussionsupporting
confidence: 85%
“…(15) CD109-positive immunoreactivity in normal tissues was also detected in restricted cells, such as myoepithelial cells of the mammary, salivary and lacrimal glands, and basal cells of the prostate. (16) Our findings, together with previous reports showing CD109 expression on hematopoietic and mesenchymal stem cell subsets, activated T lymphoblasts and platelets, and some human tumor cell lines, (1,2,4,5) demonstrate that CD109 plays a role in cell proliferation and tumor development, especially that of SCC, and that CD109 expression in normal tissues may be strictly controlled. In the present study, we assessed the significance of CD109 expression in tumor development and cell proliferation using human oral tumor tissues and cancer cell lines.…”
Section: Discussionsupporting
confidence: 79%
“…Although CD109 has been shown to be an activation antigen for T cells and platelets (24), to carry the platelet Gov alloantigen system (27), and to be expressed widely in human tissues (29), the physiological function of this protein is not known. Results from the present study linking CD109 function to regulation of TGF-␤1 signaling in vitro suggest that it may play a similar role in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…CD109 is a GPI-anchored protein, first identified using monoclonal antibodies raised against the human leukemia cell line KG1a, on activated T cells and platelets and on a subset of hematopoetic progenitor cells (23,24), with a wider distribution reported more recently (25,26). Although CD109 has been found to represent the Gov alloantigen on platelets (27), and its molecular cloning as a novel member of the ␣2macroglobulin(␣2M)/complement gene family has recently been reported (28,29), its function has remained unknown.…”
mentioning
confidence: 99%